2014
DOI: 10.1073/pnas.1315325111
|View full text |Cite
|
Sign up to set email alerts
|

Hst3 is turned over by a replication stress-responsive SCF Cdc4 phospho-degron

Abstract: Hst3 is the histone deacetylase that removes histone H3K56 acetylation. H3K56 acetylation is a cell-cycle-and damage-regulated chromatin marker, and proper regulation of H3K56 acetylation is important for replication, genomic stability, chromatin assembly, and the response to and recovery from DNA damage. Understanding the regulation of enzymes that regulate H3K56 acetylation is of great interest, because the loss of H3K56 acetylation leads to genomic instability. HST3 is controlled at both the transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…It was previously reported that Mec1 targets the H3K56ac deacetylase Hst3 to degradation (Edenberg et al, 2014). We reasoned that this degradation could explain the reduced H3K56ac and loss of homeostasis.…”
Section: The S Phase Checkpoint Stabilizes H3k56 Acetylationmentioning
confidence: 87%
See 1 more Smart Citation
“…It was previously reported that Mec1 targets the H3K56ac deacetylase Hst3 to degradation (Edenberg et al, 2014). We reasoned that this degradation could explain the reduced H3K56ac and loss of homeostasis.…”
Section: The S Phase Checkpoint Stabilizes H3k56 Acetylationmentioning
confidence: 87%
“…We reasoned that this degradation could explain the reduced H3K56ac and loss of homeostasis. To this end, we considered Hst3D97, an Hst3 allele that is resistant to the Mec1-dependent phosphorylation that leads to its degradation (Edenberg et al, 2014). This allele, however, had no effect on expression homeostasis ( Figures S5K-S5M).…”
Section: The S Phase Checkpoint Stabilizes H3k56 Acetylationmentioning
confidence: 99%
“…6,7 Degrons are usually N- or C-terminal extensions outside the catalytic domain and function when fused to ectopic substrates. 8,9 …”
mentioning
confidence: 99%
“…Four of the five sirtuins have reported roles in responding to or preventing enhanced accumulation of DNA damage. Hst3 and Hst4 deacetylate histone H3 on K56, which is deposited during DNA replication, and this deacetylation is prevented in the presence of DNA damage (Celic et al 2006;Maas et al 2006;Miller et al 2006;Edenberg et al 2014b). Levels of Hst3 and Hst4 are tightly controlled (Thaminy et al 2007;Delgoshaie et al 2014;Edenberg et al 2014b) and their absence results in persistent H3 K56 acetylation.…”
mentioning
confidence: 99%
“…Hst3 and Hst4 deacetylate histone H3 on K56, which is deposited during DNA replication, and this deacetylation is prevented in the presence of DNA damage (Celic et al 2006;Maas et al 2006;Miller et al 2006;Edenberg et al 2014b). Levels of Hst3 and Hst4 are tightly controlled (Thaminy et al 2007;Delgoshaie et al 2014;Edenberg et al 2014b) and their absence results in persistent H3 K56 acetylation. Deregulation of H3 K56 acetylation is associated with spontaneous activation of the DNA damage response and defects in DNA repair (Celic et al 2006(Celic et al , 2008Maas et al 2006;Muñoz-Galván et al 2013;Che et al 2015;Simoneau et al 2015).…”
mentioning
confidence: 99%